(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
Extraordinary mechanical properties in biological composites come from their hierarchical structures and are well seen in bones, teeth, shells etc. Nature inspired knowledge could certainly help in the design of new nanostructured materials. The current study illustrates a multi-scale nanotube model for the purpose of the structure of very large groups of carbon nanotubes (CNTs). Two different types of circular beam finite elements are used to shape bond stretching energy or to account for the potential connected to bond angle variation. Multiscale approach considers CNTs at a mesoscopic level through chains of straight cylindrical segments, where mesoscopic force field describes the interactions among the segment. Property dependence at the nanoscale results from the surface and bulk energies competition.